3D Printing of Objects with Bulk Superhydrophobicity Using Self-Foaming Polydimethylsiloxane-Based Ink - Ruifeng Jiang (9187384) (2025)
Although bulk superhydrophobic material can maintain durable superhydrophobicity by its micro–nanostructure regeneration for promising application, the 3D printing is still challenging due to the requirement of a large amount of solvent and complicated fabrication processing. Herein, a solvent-free and self-foaming polydimethylsiloxane (PDMS)-based ink is developed for 3D printing bulk superhydrophobic objects. The ink incorporates thermally expandable microspheres (EMs) and polytetrafluoroethylene (PTFE) particles, enabling hierarchical roughness and low surface energy throughout the bulk. During thermal curing, EMs generate cellular pores (20–50 μm) and disrupt the formation of a dense skin layer in the cured PDMS ink, while PTFE particles migrate to the surface, achieving a Cassie-state superhydrophobicity with a water contact angle of 155° and a sliding angle of 9°. The printed foam exhibits exceptional durability, retaining superhydrophobicity after 1000 abrasion cycles due to self-similar porous structures. Rheological optimization ensures printability, and the lightweight foam (density of 0.16 g/cm3) demonstrates versatile applications, including waterproofing, oil–water separation, and waterproof buoyancy carrier for a drone (supporting 7× its weight). This work presents an environmentally benign and facile strategy for fabricating robust, bulk superhydrophobic materials with scalable 3D printing, advancing their potential in sustainable industrial and environmental applications.